Regional information infrastructure : a development strategy for CARICOM - Stone, Martha ([IDB] [Washington]US, 1996)
Presents a review of the experiences of several countries that have successfully developed national strategies for creating a new Information Society. Reviews the current situation in selected CARICOM member states. Concludes with a set of key issues and recommendations that are essential for the establishment of a development strategy for a regional information infrastructure for the English-speaking member states of CARICOM.